Changes in electroencephalogram pattern by ice cube cold pressor stimulus. (1st January 2012) - Kumar, Sanjeev; Kumar, Amod; Trikha, Anjan; Anand, Sneh
Central nervous system (CNS) is the master control of the body. Electroencephalogram (EEG) is the signal generated by brain due to the activity of different neurons. For many past years, EEG has been used to find out the state of the patient during surgery. Many depth of anaesthesia (DoA) monitor based on EEG processing are available off-the-shelf which gives the hypnosis state of the patient during surgery but none of them gives any information about pain experienced by the patient during surgery or post surgery. As the CNS is the master control of the body, the analgesia effect of patient during surgery can also be extracted from EEG of the patient. For this purpose, EEG data of 12 volunteer has been recorded from parietal region of the brain during relaxed state and during the pain stimulation given by ice cube cold water. The recorded raw EEG data was filtered by a low pass filter (fc = 45 Hz) and processed to extract different identified EEG parameters. Total of 21 EEG parameters were computed for two sets of EEG data. Stepwise discriminant analysis (SDA) was implemented to pruning the best parameters. One parameter 'Activity' gives a consistent change in all subjects. This parameter of EEG can be further used to find out the pain experienced by the patient during surgical procedure to avoid intra surgical awareness.